2020
DOI: 10.3390/jcm9061849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Type 2 Diabetes on the Inner Retinal Layer and Macular Microvasculature: An Optical Coherence Tomography Angiography Study

Abstract: Purpose: To identify the effects of prolonged type 2 diabetes (T2DM) on macular microcirculation and the inner retinal layer in diabetic eyes without clinical diabetic retinopathy (DR). Methods: 97, 92, and 57 eyes in the control, patients with T2DM < 10 years (DM group one), and patients with T2DM ≥ 10 years (DM group two) were enrolled. The ganglion cell-inner plexiform layer (GC-IPL) thickness and superficial vessel density (VD) were compared. Linear regression analyses were performed to identify factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 45 publications
(58 reference statements)
1
36
0
2
Order By: Relevance
“…Previous longitudinal studies reported that age was not a significant factor associated with changes in the pRNFL thickness of T2DM patients 10,38 . Lee et al 42 also reported that age was not a significant factor associated with retinal microvasculature in T2DM. These studies all reported that DM duration was a significant factor associated with the inner retinal damage by DRN and impairment of the retinal microvasculature.…”
Section: Discussionmentioning
confidence: 95%
“…Previous longitudinal studies reported that age was not a significant factor associated with changes in the pRNFL thickness of T2DM patients 10,38 . Lee et al 42 also reported that age was not a significant factor associated with retinal microvasculature in T2DM. These studies all reported that DM duration was a significant factor associated with the inner retinal damage by DRN and impairment of the retinal microvasculature.…”
Section: Discussionmentioning
confidence: 95%
“…These results were similar to our previous study that patients with prolonged T2DM exhibited thinner macular GC-IPL and more severe impairment of macular microvasculature. 21 Neuronal death and glial dysfunction by diabetic retinal neurodegeneration can cause a breakdown of the blood-retinal barrier, vasoregression, and impairment of neurovascular coupling, which may result in early microvascular impairment. 16 As the damages caused by such diabetic retinal neurodegeneration accumulated, the patients with prolonged T2DM would show more severely damaged microvasculature similar to pRNFL thinning.…”
Section: Discussionmentioning
confidence: 99%
“… 4 An autoregulatory response of the neurovascular unit to complex circulatory and neural cues is essential to regulate blood flow through the inner retina owing to the lack of autonomic innervation of the intraretinal vasculature, so disruption of the neurovascular unit by DRN would affect the impaired macular microcirculation. 3 , 4 , 7 , 24 Therefore, even in the absence of signs related to DR, such as microaneurysm or retinal hemorrhage, patients with T2DM would have impaired macular microcirculation and microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients showing DR changes, such as retinal hemorrhage, hard exudates, and cotton wool spots, require careful observation for various DR-related complications. Meanwhile, anatomical and functional impairments of the retina have been reported recently in diabetic patients without clinical DR. Diabetic retinal neurodegeneration (DRN), which causes accelerated inner retinal reduction over time, is a representative type of retinal damage preceding DR. 2 6 Additionally, as detailed observation of microvasculature at high resolution has become possible using optical coherence tomography angiography (OCTA), impairments of peripapillary and macular microvasculature have been reported in diabetic patients without DR. 7 , 8 …”
mentioning
confidence: 99%